2017
DOI: 10.1111/bju.13782
|View full text |Cite
|
Sign up to set email alerts
|

Detection and oncological effect of circulating tumour cells in patients with variant urothelial carcinoma histology treated with radical cystectomy

Abstract: CTC are detectable in about a quarter of patients with pure or variant UCB histology before RC, and represent an independent predictor for outcomes, when adjusting for histological subtype. In addition, our prospective data confirm the unfavourable influence of non-squamous cell-differentiated UCB on outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 30 publications
0
23
1
Order By: Relevance
“…I read this article from Hamburg‐Eppendorf with great interest . The treatment of invasive urothelial carcinoma has not significantly progressed in the last 30 years, with survivals currently that are little changed since the first introduction of multi‐drug platinum‐based chemotherapy in the 1980s.…”
contrasting
confidence: 64%
“…I read this article from Hamburg‐Eppendorf with great interest . The treatment of invasive urothelial carcinoma has not significantly progressed in the last 30 years, with survivals currently that are little changed since the first introduction of multi‐drug platinum‐based chemotherapy in the 1980s.…”
contrasting
confidence: 64%
“…The presence of CTCs was associated with lymphovascular invasion, microvascular invasion, and positive soft tissue surgical margins, but not with lymph node metastasis. A weak association was found with pathological T stage (p = 0.065), and in a later paper (encompassing three extra patients) [22] the association became significant (p = 0.041). CTC-positive patients who underwent RC, with or without AC, had poorer recurrence-free survival (RFS; either local recurrence or metastatic recurrence) than CTC-negative patients (2- , p < 0.001).…”
Section: Ctc Detection With the Cellsearch Systemmentioning
confidence: 78%
“…Multiple groups confirmed the detection of CTCs in nmBC patients in small patient sets [17][18][19]. The largest dataset on CTCs in nmBC patients to date has been published by the Hamburg group on several occasions [20][21][22][23]. Their most recent analysis encompassed 185 nmBC patients (69% with pathological MIBC) undergoing RC without NAC, of whom 50 patients received AC (patients with !…”
Section: Ctc Detection With the Cellsearch Systemmentioning
confidence: 86%
“…Three and 5 year DSSs were found to be 71.9±2% and 67.9±2%; 27.6±9% and 18.4±8% for the groups, respectively. Recently, Soave et al [14] reported the relationship between preoperative circulating tumor cells (CTC) count, BC histopathology and survival of 188 patients. They reported that patients with non-squamous differentiation had inferior recurrence free survival (RFS), compared to patients with PUH and patients with squamous cell differentiation (p=0.016).…”
Section: Discussionmentioning
confidence: 99%